Preparation method and application of a moso bamboo-based silicon-titanium composite carbon electrode material
Patent Information
- Application Number
- CN202511143860.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-08-15
AI Technical Summary
现有技术主要通过热解碳化结合活化工艺进行改性:分段控温热解可实现组分定向转化,其中蒸汽活化能使比表面积达到1182 m²/g,而KOH化学活化虽可扩增介孔体积至1.044 cm³/g,但需维持KOH/碳质量比>3:1的高消耗量,并产生含碱废液;功能化改性方面,氮掺杂竹炭可实现475 F/g的比电容,但高温掺杂导致sp²/sp³杂化碳比例失衡,金属氧化物复合策略,虽将比电容提升至872 F/g,却在5000次循环后出现显著容量衰减
本发明通过原位构建SiO/TiO核壳结构与碳基褶皱片层的协同作用,突破传统生物质电极的能量密度瓶颈,在典型电解体系中实现远高于商业超级电容器的能量密度水平,有效满足高能耗场景需求。
Smart Images

Figure CN120998698B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrode materials, and more specifically to a method for preparing and applying a bamboo-based silicon-titanium composite carbon electrode material. Background Technology
[0002] Supercapacitors, with their ultra-high power density and long cycle life, have become key components for grid peak shaving, but their commercial application is limited by their low energy density. Biomass-derived carbon materials have become an important research direction due to their sustainability and structural designability. Moso bamboo, an agricultural waste with an annual output of over 50 million tons in southern my country, has a unique three-dimensional porous framework composed of cellulose, hemicellulose, and lignin. It possesses the mechanical stability provided by high cellulose content, the inhibitory effect of low oxygen content on pyrolysis side reactions, and the enhancing effect of silicon in the ash on carrier mobility. Existing technologies mainly modify bamboo charcoal through a combination of pyrolysis carbonization and activation processes. Segmented temperature-controlled pyrolysis can achieve directional conversion of components. Steam activation can increase the specific surface area to 1182 m² / g, while KOH chemical activation can expand the mesopore volume to 1.044 cm³ / g, but requires maintaining a high consumption of KOH / carbon mass ratio >3:1 and generates alkaline waste liquid. In terms of functionalization modification, nitrogen-doped bamboo charcoal can achieve a specific capacitance of 475 F / g, but high-temperature doping leads to an imbalance in the sp² / sp³ hybrid carbon ratio. The metal oxide composite strategy, although increasing the specific capacitance to 872 F / g, shows significant capacity decay after 5000 cycles.
[0003] However, existing technologies still suffer from the following key limitations: First, energy density is a significant bottleneck; the optimal bamboo-based electrode in an asymmetric system has an energy density of only 380 mAh / g, which is insufficient for high-energy-consumption scenarios. Second, cycle stability is inadequate; the metal oxide and carbon substrate mainly bind through physical adsorption, and the weakening of interfacial bonding during cycling leads to the shedding of active materials. Third, the preparation process suffers from high pollution and high cost; KOH activation generates highly alkaline waste liquid, increasing environmental treatment costs, and precious metal catalysts account for more than 40% of the total electrode cost. Furthermore, the structural design suffers from an excessively high micropore ratio, hindering ion diffusion at high rates, and functional modification is also limited by the poor thermal stability of doping elements. Current technologies are caught in an "impossible triangle" of difficulty in synergistically optimizing energy density, power density, and cycle life, necessitating the development of innovative solutions that combine efficient interface engineering with green preparation processes. Summary of the Invention
[0004] To address the aforementioned technical problems in the prior art, this invention provides a method for preparing a bamboo-based silicon-titanium composite carbon electrode material, comprising the following steps: (1) Raw material pretreatment: crush the bamboo into particles with a diameter of <2 mm, soak it in a mixed salt solution containing copper ions and zinc ions for 8-12 h, wash and dry it to obtain pretreated bamboo powder. (2) Synchronous pyrolysis and functionalization composite: Pretreated bamboo powder and titanium source are mixed at a mass ratio of (1-2):1, heated to the target temperature at 10-50℃ / min under an inert atmosphere, and kept at the temperature for 30-60 min to obtain composite carbon material containing core-shell structured silicon titanium oxide. (3) Electrode preparation: The composite carbon material containing core-shell silicon titanium oxide obtained in step (2), conductive agent and binder are prepared into a slurry in a mass ratio of (6-8):(1-3):(0.5-1.5), coated on activated carbon cloth, and then freeze-dried or directionally frozen in liquid nitrogen.
[0005] In step (1), the concentrations of CuSO4 and ZnSO4 in the mixed salt solution are both 0.10-0.20 mol / L.
[0006] The target temperature in step (2) includes: first stage pyrolysis: 200-300℃ to decompose the titanium source into titanium dioxide nanoparticles embedded in the carbon skeleton; second stage pyrolysis: 700-900℃ to react the silicon dioxide in the bamboo ash with the titanium dioxide to generate core-shell structured silicon titanium oxide.
[0007] In step (2), the titanium source is tetraethyl titanate, and the mass ratio of bamboo powder to titanium source is 3:2; the second stage pyrolysis temperature is 800℃, the heating rate is 20-40℃ / min, and the isothermal time is 45 min.
[0008] In step (2), the shell thickness of the core-shell structured silicon titanium oxide is 1-3 nm; the mesoporous rate of the composite carbon material is 70-80%.
[0009] In step (3), the freeze-drying process involves pre-freezing at -40 to -60°C for 24 hours.
[0010] The step (3) of liquid nitrogen directional freezing involves vertically immersing the carbon cloth coated with slurry into liquid nitrogen at -196°C to freeze it, thereby inducing the formation of a vertical pore array.
[0011] On the other hand, the present invention provides a supercapacitor electrode, which uses a composite carbon material containing a core-shell structured silicon titanium oxide prepared by the method as the active material, and satisfies the following in 0.5 mol / L sulfuric acid electrolyte: specific capacitance ≥110 F / g; capacity retention ≥100% after 10,000 cycles at a current density of 10 A / g; and energy density ≥15 Wh / kg.
[0012] The present invention has the following advantages over the prior art: This invention breaks through the energy density bottleneck of traditional biomass electrodes by constructing the synergistic effect of SiO / TiO core-shell structure and carbon-based wrinkled sheets in situ. It achieves an energy density level far exceeding that of commercial supercapacitors in typical electrolysis systems, effectively meeting the needs of high-energy-consumption scenarios.
[0013] On the other hand, based on the strong chemical bonding mechanism between SiO / TiO and the carbon substrate and the stable mesoporous framework formed by the self-generated melt pore expansion, the electrode exhibits excellent structural integrity during high current cycling, completely solving the capacity decay problem caused by the shedding of metal oxides, and the cycle life is significantly better than that of existing metal composite electrode systems.
[0014] Finally, the inherent components of biomass are used to achieve self-activation and pore expansion, completely avoiding the dependence on corrosive chemicals and precious metal catalysts in traditional processes, thus eliminating alkaline wastewater pollution at the source; the simultaneous pyrolysis-composite design significantly shortens the process flow and significantly reduces energy consumption and environmental treatment costs. Attached Figure Description
[0015] Figure 1 These are the cyclic voltammetric characteristic curves of Example 1 and Comparative Example 1; Figure 2 These are the cyclic voltammetric characteristic curves of Example 2 and Comparative Example 2; Figure 3 These are the cyclic voltammetric characteristic curves of Example 3 and Comparative Example 3; Figure 4 These are the constant current charge-discharge curves of Example 1 and Comparative Example 1, and Example 2 and Comparative Example 2; Figure 5 These are the constant current charge-discharge curves of Example 3 and Comparative Example 3; Figure 6 These are the constant current charge-discharge curves of Example 3 and Comparative Example 3; Figure 7 These are the constant current charge-discharge curves of Example 3 and Comparative Example 3; Figure 8 These are the AC impedance curves of Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, and Example 3 and Comparative Example 3; Figure 9 Electron micrograph of Comparative Example 3; Figure 10 Energy spectrum of Comparative Example 3; Figure 11 Electron micrograph of Example 3; Figure 12 This is the energy spectrum of Example 3. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of this invention clearer, the invention is described below with reference to specific embodiments shown in the accompanying drawings. However, it should be understood that these descriptions are merely exemplary and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concept of the invention.
[0017] This invention provides a method for preparing and applying a bamboo-based silicon-titanium composite carbon electrode material. The method includes the following steps: (1) Raw material pretreatment: crush the bamboo into particles with a diameter of <2 mm, soak it in a mixed salt solution containing copper ions and zinc ions for 8-12 h, wash and dry it to obtain pretreated bamboo powder. (2) Synchronous pyrolysis and functionalization composite: Pretreated bamboo powder and titanium source are mixed at a mass ratio of (1-2):1, heated to the target temperature at 10-50℃ / min under an inert atmosphere, and kept at the temperature for 30-60 min to obtain composite carbon material containing core-shell structured silicon titanium oxide. (3) Electrode preparation: The composite carbon material containing core-shell silicon titanium oxide obtained in step (2), conductive agent and binder are prepared into a slurry in a mass ratio of (6-8):(1-3):(0.5-1.5), coated on activated carbon cloth, and then freeze-dried or directionally frozen in liquid nitrogen.
[0018] In step (1), the concentrations of CuSO4 and ZnSO4 in the mixed salt solution are both 0.10-0.20 mol / L. In step (2), the target temperatures include: a first-stage pyrolysis at 200-300℃ to decompose the titanium source into titanium dioxide nanoparticles embedded in a carbon framework; and a second-stage pyrolysis at 700-900℃ to react the silicon dioxide in the bamboo ash with the titanium dioxide to generate a core-shell structured silicon titanium oxide. In step (2), the titanium source is tetraethyl titanate, and the mass ratio of bamboo powder to titanium source is 3:2; the second-stage pyrolysis temperature is 800℃, the heating rate is 20-40℃ / min, and the isothermal time is 45 min. In step (2), the shell thickness of the core-shell structured silicon titanium oxide is 1-3 nm; the mesoporous rate of the composite carbon material is 70-80%. In step (3), freeze-drying involves pre-freezing at -40 to -60℃ for 24 h. The step (3) of liquid nitrogen directional freezing involves vertically immersing the carbon cloth coated with slurry into liquid nitrogen at -196°C to freeze it, thereby inducing the formation of a vertical pore array.
[0019] A supercapacitor electrode uses a composite carbon material containing a core-shell structured silicon-titanium oxide prepared by the method as the active material, which meets the following requirements in 0.5 mol / L sulfuric acid electrolyte: specific capacitance ≥110 F / g; capacity retention ≥100% after 10,000 cycles at a current density of 10 A / g; and energy density ≥15 Wh / kg.
[0020] Example 1
[0021] 1. Raw material pretreatment
[0022] Moso bamboo raw materials were selected, crushed, washed to remove impurities, and dried in an oven at 110℃ to constant weight, then crushed into particles with a diameter <2mm. The bamboo powder was soaked in a 0.15 mol / L CuSO4 and ZnSO4 mixed solution for 12 h to enhance the porosity of the bamboo through ion exchange. It was then rinsed three times with distilled water and dried to obtain pretreated bamboo powder. This process removes metallic impurities from the lignin while retaining the natural silicon element in the bamboo (ash content contains approximately 2.5 wt% SiO2), providing a silicon source for subsequent in-situ SiO2 formation.
[0023] 2. Simultaneous pyrolysis and functionalization composite
[0024] (1) Mix the pretreated bamboo powder and tetraethyl titanate at a mass ratio of 3:2 until homogeneous; (2) Place it in a tubular furnace quartz boat and introduce nitrogen gas (flow rate 50 mL / min). (3) The temperature was increased to 200℃ at 30℃ / min and held at the temperature for 45 min to obtain a composite carbon material containing core-shell structured silicon titanium oxide (SiO / TiO@C-1 active material).
[0025] 3. Electrode preparation
[0026] (1) Take SiO / TiO@C active material, conductive carbon black and PVDF binder and mix them in a mass ratio of 7:2:1; first take the active material and NMP solvent and ultrasonically disperse them at 60℃ for 30 min; then take PVDF and NMP and ultrasonically dissolve them at 60℃ for 1 h; mix and homogenize.
[0027] (2) The carbon cloth is immersed in 17% Solution 1.5 h; rinse 5 times with deionized water, sonicate with anhydrous ethanol for 20 min, and dry at 60℃ for 12 h; (3) The slurry was coated on carbon cloth (load 0.003 g / cm²); freeze-dry at -50℃ for 24 h to fix the microstructure.
[0028] Example 2
[0029] In step 2, the temperature is increased to 300℃ at a rate of 30℃ / min and held at that temperature for 45 min to obtain a composite carbon material containing a core-shell structured silicon titanium oxide (SiO / TiO@C-3 active material). The other steps are the same as in Example 1.
[0030] Example 3
[0031] In step 2, the temperature is increased to 800℃ at a rate of 30℃ / min in a low-temperature zone and held at that temperature for 45 min to obtain a composite carbon material containing a core-shell structured silicon titanium oxide (SiO / TiO@C-13 active material). In step 3, the loading amount is 0.045 g / cm³. 2, The other steps are the same as in Example 1.
[0032] Low-temperature range (200-300℃): Tetraethyl titanate decomposes into TiO nanoparticles (5-10 nm in size), which embed into the microporous structure of bamboo charcoal, forming a TiO@C primary composite. High-temperature range (800℃): SiO2 and TiO2 in bamboo ash react through a solid-state reaction to generate a core-shell structure SiO / TiO (XPS verification of Ti-O-Si bonding), while KOH (inherent potassium element in bamboo) activates and generates mesopores (pore size 2-50 nm), with a mesopore rate of 75.5%.
[0033] In this invention, K2O in bamboo ash reacts with carbon (6KOH + 2C → 2K + K2CO3 + 3H2) to generate a self-generated K2CO3 melt (891℃), expanding pores while avoiding external KOH contamination. The mesopore volume reaches 1.172 cm³ / g (BET verification), enabling this application to replace traditional KOH activation. In the high-temperature stage (800℃), SiO2 and TiO2 undergo a solid-state reaction to form Ti-O-Si bonds (XPS verification), solving the problem of interface detachment.
[0034] Example 4
[0035] The mass ratio of bamboo powder to tetraethyl titanate was 1:1; the heating rate was 10℃ / min (at a constant temperature of 800℃); the holding time was 60min; and other steps were the same as in Example 1.
[0036] Example 5
[0037] The mass ratio of bamboo powder to tetraethyl titanate was 2:1; the heating rate was 50℃ / min (at a constant temperature of 800℃); the holding time was 30min; and other steps were the same as in Example 1.
[0038] Example 6
[0039] In step (1), the concentrations of CuSO4 and ZnSO4 in the mixed salt solution are both 0.10 mol / L, and the other steps are the same as in Example 1.
[0040] Example 7
[0041] In step (1), the concentrations of CuSO4 and ZnSO4 in the mixed salt solution are both 0.15 mol / L, and the other steps are the same as in Example 1.
[0042] Example 8
[0043] In step (1), the concentrations of CuSO4 and ZnSO4 in the mixed salt solution are both 0.20 mol / L, and the other steps are the same as in Example 1.
[0044] Example 9
[0045] In this embodiment, the ratio of SiO / TiO@C active material: conductive carbon black: PVDF is 8:1.5:0.5, and the other steps are the same as in Example 1.
[0046] Example 10
[0047] In this embodiment, the ratio of SiO / TiO@C active material: conductive carbon black: PVDF is 6:1:0.5, and the other steps are the same as in Example 1.
[0048] Example 11
[0049] In this embodiment, the ratio of SiO / TiO@C active material: conductive carbon black: PVDF is 8:3:1.5, and the other steps are the same as in Example 1.
[0050] Example 12
[0051] The same process is applicable to corn stalks (cellulose ≥ 38%), sugarcane bagasse (hemicellulose 28%), and rice husk ash ( 20 wt%
[0052] Comparative Example 1
[0053] 1. Pre-treated bamboo powder and KOH are mixed at a mass ratio of 1:3; 2. The composite carbon material (SiO@C active material) was obtained by heating to 200℃ at 30℃ / min under nitrogen atmosphere and holding at a constant temperature of 45℃.
[0054] 3. Electrode preparation
[0055] (1) Take SiO@C active material, conductive carbon black and PVDF binder and mix them in a mass ratio of 7:2:1; first take the active material and NMP solvent and ultrasonically disperse them at 60℃ for 30 min; then take PVDF and NMP and ultrasonically dissolve them at 60℃ for 1 h; mix and homogenize.
[0056] (2) The carbon cloth is immersed in 17% Solution 1.5 h; rinse 5 times with deionized water, sonicate with anhydrous ethanol for 20 min, and dry at 60℃ for 12 h; (3) The slurry was coated on carbon cloth (load 0.003 g / cm²); freeze-dry at -50℃ for 24 h to fix the microstructure.
[0057] Supercapacitor electrode performance verification in examples and comparative models
[0058] Test conditions: Electrolyte: 0.5 mol / L H2SO4; Voltage window: -0.3~0.4 V; Active substance loading: 0.003 g / cm².
[0059] Comparative Example 2
[0060] In step 2, the temperature was increased to 300℃ at 30℃ / min and held at that temperature for 45 min to obtain the composite carbon material (SiO@C active material). In step 3, the loading amount was 0.003 g / cm², and the other steps were the same as those in Comparative Example 1.
[0061] Comparative Example 3
[0062] In step 2, the temperature is increased to 800℃ at a rate of 30℃ / min in the low-temperature section and held at that temperature for 45 min to obtain the composite carbon material (SiO@C active material). In step 3, the loading amount is 0.045 g / cm², and the other steps are the same as those in Comparative Example 1.
[0063] Results comparison (1 A / g): Specific capacitance (F / g) 119.3 79.9 15.7% Cycle retention rate (%) 108% 104% 0.84% Energy density (Wh / Kg) 15.94 10.23 21.3% Power density (kW / kg) 1.61 1.03 32.2% Charge transfer resistance (Ω) 0.15 0.59 -20.5%
[0064] This patented technology significantly improves the overall performance of electrode materials through an innovative preparation method. The specific technical effects are as follows: 1. Breakthrough in energy density: Example 3 achieved an energy density of 15.94 Wh / kg under pyrolysis conditions at 800℃, which is 21.3% higher than Comparative Example 3 (10.23 Wh / kg), breaking through the energy density bottleneck of traditional biomass electrodes and meeting the needs of high-energy-consumption scenarios.
[0065] 2. Increased power density: The power density of Example 3 is 1.61 kW / kg, which is 32.2% higher than that of Comparative Example 3 (1.03 kW / kg). The stable framework structure with a mesoporous ratio of 75.5% accelerates ion diffusion and solves the problem of ion transport obstruction at high magnification.
[0066] 3. Enhanced cycle stability: After multiple cycles at a current density of 1 A / g, the capacity retention rate is ≥100%, and the cycle retention rate in Example 3 reaches 108%. The core-shell structure (SiO / TiO) enhances the interface stability through Ti-O-Si chemical bonding, which completely solves the capacity decay caused by the shedding of metal oxides.
[0067] 4. Optimized charge transfer efficiency: The charge transfer resistance of Example 3 is as low as 0.15Ω, which is 20.5% lower than that of Comparative Example 3 (0.59Ω). The synergistic effect of SiO / TiO core-shell structure and carbon substrate improves electron conduction rate.
[0068] 5. Green preparation process: Utilizing the inherent potassium element in bamboo to achieve self-generation, avoiding corrosive chemicals such as KOH, reducing KOH consumption by 0.5 tons per ton of bamboo, eliminating alkaline waste liquid discharge, and shortening the preparation cycle to 45 minutes through simultaneous pyrolysis process, significantly reducing energy consumption and environmental costs.
[0069] Figure 1 These are the cyclic voltammetric characteristic curves of Example 1 and Comparative Example 1; where Figure 1 (1) represents the cyclic voltammetric characteristic curves of SiO / TiO@C-1 at 200℃ with scan rates of 0.005V / s, 0.01V / s, and 0.02V / s; (2) represents the cyclic voltammetric characteristic curves of SiO / TiO@C-1 at 200℃ with scan rates of 0.04V / s, 0.06V / s, and 0.08V / s; (3) represents the cyclic voltammetric characteristic curves of Blank Control-2 in the blank experiment at 200℃ with scan rates of 0.005V / s, 0.01V / s, and 0.02V / s; and (4) represents the cyclic voltammetric characteristic curves of Blank Control-2 in the blank experiment at 200℃ with scan rates of 0.06V / s and 0.08V / s.
[0070] Figure 2 These are the cyclic voltammetric characteristic curves of Example 2 and Comparative Example 2; where Figure 1 (1) represents the cyclic voltammetric characteristic curves of SiO / TiO@C-3 at 300℃ with scan rates of 0.005V / s, 0.01V / s, and 0.02V / s; (2) represents the cyclic voltammetric characteristic curves of SiO / TiO@C-3 at 300℃ with scan rates of 0.04V / s, 0.06V / s, and 0.08V / s; (3) represents the cyclic voltammetric characteristic curves of Blank Control-4 in the blank experiment at 300℃ with scan rates of 0.005V / s, 0.01V / s, and 0.02V / s; and (4) represents the cyclic voltammetric characteristic curves of Blank Control-4 in the blank experiment at 300℃ with scan rates of 0.04V / s, 0.06V / s, and 0.08V / s.
[0071] Figure 3 These are the cyclic voltammetric characteristic curves of Example 3 and Comparative Example 3; where Figure 1(1) represents the cyclic voltammetric characteristic curves of SiO / TiO@C-13 at 800℃ with scan rates of 0.005V / s, 0.01V / s, and 0.02V / s; (2) represents the cyclic voltammetric characteristic curves of SiO / TiO@C-13 at 800℃ with scan rates of 0.04V / s, 0.06V / s, 0.08V / s, and 0.1V / s; (3) represents the cyclic voltammetric characteristic curves of Blank Control-14 in the blank experiment at 800℃ with scan rates of 0.005V / s, 0.01V / s, and 0.02V / s; and (4) represents the cyclic voltammetric characteristic curves of Blank Control-14 in the blank experiment at 800℃ with scan rates of 0.04V / s, 0.06V / s, 0.08V / s, and 0.1V / s.
[0072] Figure 4 These are the constant current charge-discharge curves of Example 1 and Comparative Example 1, and Example 2 and Comparative Example 2; wherein Figure 1 In the figure, (1) represents the constant current charge-discharge curve of SiO / TiO@C-1 at a current density of 1A / g at 200℃, (2) represents the constant current charge-discharge curve of Blank Control-2 in the blank experiment at a current density of 1A / g at 200℃, (3) represents the constant current charge-discharge curve of SiO / TiO@C-3 at a current density of 1A / g at 300℃, and (4) represents the constant current charge-discharge curve of Blank Control-4 in the blank experiment at a current density of 1A / g at 300℃.
[0073] Figure 5 These are the constant current charge-discharge curves of Example 3 and Comparative Example 3; wherein Figure 1 (1) represents the constant current charge-discharge curve of SiO / TiO@C-13 at 800℃ and a current density of 1A / g; (2) represents the constant current charge-discharge curve of Blank Control-14 in the blank experiment at 800℃ and a current density of 1A / g; (3) represents the constant current charge-discharge curve of SiO / TiO@C-13 at 800℃ and a current density of 2A / g; and (4) represents the constant current charge-discharge curve of Blank Control-14 in the blank experiment at 800℃ and a current density of 2A / g.
[0074] Figure 6 These are the constant current charge-discharge curves of Example 3 and Comparative Example 3; wherein Figure 1In the figure, (1) represents the constant current charge-discharge curve of SiO / TiO@C-13 at 800℃ and a current density of 3A / g, (2) represents the constant current charge-discharge curve of Blank Control-14 in the blank experiment at 800℃ and a current density of 3A / g, (3) represents the constant current charge-discharge curve of SiO / TiO@C-13 at 800℃ and a current density of 4A / g, and (4) represents the constant current charge-discharge curve of Blank Control-14 in the blank experiment at 800℃ and a current density of 4A / g.
[0075] Figure 7 These are the constant current charge-discharge curves of Example 3 and Comparative Example 3; wherein Figure 1 In the figure, (1) represents the constant current charge-discharge curve of SiO / TiO@C-13 at a current density of 5A / g at 800℃, and (2) represents the constant current charge-discharge curve of Blank Control-14 in the blank experiment at a current density of 5A / g at 800℃.
[0076] This invention solves the industry problems of low energy density, poor cycle stability and high pollution in the preparation of biomass electrode materials through an integrated design of "raw material pretreatment-in-situ composite-green activation". It achieves a synergistic breakthrough in high performance and sustainability, and provides a reliable technical path for the large-scale application of supercapacitors.
[0077] This invention uses bamboo waste as raw material and pre-treats it by soaking in a metal salt solution. This removes impurities while retaining the inherent silicon source of the bamboo, providing a basis for subsequent in-situ composite. This method combines resource recycling with low cost.
[0078] Pretreated bamboo powder is mixed with tetraethyl titanate and subjected to gradient pyrolysis under a nitrogen atmosphere to achieve: in-situ formation of a SiO / TiO core-shell structure; in the low-temperature stage, TiO2 nanoparticles are generated and embedded in a carbon framework; in the high-temperature stage (800℃), the bamboo ash SiO2 and TiO2 form a core-shell interface through a solid-state reaction Ti-O-Si bonding, significantly enhancing ion diffusion efficiency. This invention utilizes the inherent potassium element in bamboo to react at high temperatures to generate potassium carbonate melt, expanding mesopores and completely avoiding exogenous KOH contamination.
[0079] On the other hand, a composite carbon material containing core-shell silicon-titanium oxide (SiO / TiO@C active material) is mixed with a conductive agent and a binder in a 7:2:1 ratio to form a slurry. This slurry is then freeze-dried to fix the microstructure, forming wrinkled graphene sheets that synergistically improve conductivity. Directional freezing using an ice template can further construct a vertical pore array, shortening the ion diffusion time.
[0080] The electrochemical performance of the electrode prepared by the method described in this invention is significantly improved. Furthermore, this invention eliminates highly polluting activators and achieves zero chemical waste discharge through the self-generated potassium carbonate in bamboo, saving 0.5 tons of KOH consumption per ton of bamboo. The process cycle is shortened, significantly reducing energy consumption and costs. Charge transfer resistance is reduced, and the ion diffusion coefficient is significantly improved.
[0081] Finally, the method described in this invention has universal applicability to raw materials, and can be extended to cellulose-rich agricultural wastes such as corn stalks and sugarcane bagasse. The electrode produced by this invention has high energy density, ultra-long cycle life, and environmental protection characteristics, making it suitable for high-demand energy storage scenarios such as electric vehicles and smart grids, and promoting the high-value utilization of biomass resources under the "dual-carbon" strategy.
Claims
1. A method for preparing a bamboo-based silicon-titanium composite carbon electrode material, characterized in that, Includes the following steps: (1) Raw material pretreatment: crush the bamboo into particles with a diameter of <2 mm, soak it in a mixed salt solution containing copper ions and zinc ions for 8-12 h, wash and dry it to obtain pretreated bamboo powder. (2) Simultaneous pyrolysis and functionalization composite: Pretreated bamboo powder and titanium source are mixed at a mass ratio of (1-2):1, heated to the target temperature at 10-50℃ / min under an inert atmosphere, and kept at the temperature for 30-60 min to obtain a composite carbon material containing core-shell structured silicon titanium oxide. The target temperature in step (2) includes: first stage pyrolysis: 200-300℃ to decompose the titanium source into titanium dioxide nanoparticles embedded in the carbon skeleton; second stage pyrolysis: 700-900℃ to react silicon dioxide and titanium dioxide in bamboo ash to generate core-shell structured silicon titanium oxide. (3) Electrode preparation: The composite carbon material containing core-shell silicon titanium oxide obtained in step (2), conductive agent and binder are prepared into a slurry in a mass ratio of (6-8):(1-3):(0.5-1.5), coated on activated carbon cloth, and then freeze-dried or directionally frozen in liquid nitrogen.
2. The method for preparing bamboo-based silicon-titanium composite carbon electrode material according to claim 1, characterized in that, In step (1), the concentrations of CuSO4 and ZnSO4 in the mixed salt solution are both 0.10-0.20 mol / L.
3. The method for preparing bamboo-based silicon-titanium composite carbon electrode material according to claim 1, characterized in that, In step (2), the titanium source is tetraethyl titanate, and the mass ratio of bamboo powder to titanium source is 3:2; the second stage pyrolysis temperature is 800℃, the heating rate is 20-40℃ / min, and the isothermal time is 45 min.
4. The method for preparing bamboo-based silicon-titanium composite carbon electrode material according to claim 1, characterized in that, In step (2), the shell thickness of the core-shell structured silicon titanium oxide is 1-3 nm; the mesoporous rate of the composite carbon material is 70-80%.
5. The method for preparing bamboo-based silicon-titanium composite carbon electrode material according to claim 1, characterized in that, In step (3), the freeze-drying process involves pre-freezing at -40 to -60°C for 24 hours.
6. The method for preparing bamboo-based silicon-titanium composite carbon electrode material according to claim 1, characterized in that, The step (3) of liquid nitrogen directional freezing involves vertically immersing the carbon cloth coated with slurry into liquid nitrogen at -196°C to freeze it, thereby inducing the formation of a vertical pore array.
7. A supercapacitor electrode, characterized in that, The composite carbon material containing core-shell structured silicon titanium oxide prepared by the method described in any one of claims 1-6 is used as the active material, and it meets the following requirements in 0.5 mol / L sulfuric acid electrolyte: specific capacitance ≥110 F / g; capacity retention ≥100% after 10,000 cycles at a current density of 10 A / g; and energy density ≥15 Wh / kg.
Citation Information
Patent Citations
Dye mesoporous adsorbent taking rice hulls as templates and silicon sources and preparation method thereof
CN102125820A
Bamboo-inspired nanostructure design for flexible, foldable and twistable energy storage devices
US20170125174A1